THU0349 Assessment of dry eye symptoms in primary fbromyalgia. (23rd January 2014) - Antivalle, M.; Battellino, M.; Batticciotto, A.; Ditto, M.C.; Mutti, A.; Varisco, V.; Atzeni, F.; Sarzi-Puttini, P.
Abstract : Background: While dry eye symptoms and signs have been frequently reported in fibromyalgia patients, no study so far has specifically investigated the concordance between subjective symptoms and objective findings in this population. Objectives: Aim of this study was to assess to whether, in FM patients, dry eye subjective symptoms are correlated to a real reduction of tear production, or mainly reflect a state of altered perception. Methods: 158 patients were studied, 66 with fibromyalgia (FM: 62 F, 4 M, mean age 41.83 yrs) and 92 control subjects affected by miscellaneous rheumatic diseases (Controls: 81 F, 11 M, mean age 42.26 yrs). All patients completed the questionnaire used in the diagnosis of Sjögren's syndrome (SQ) (1), and the McMonnies dry eye questionnaire (McM) (2). Schirmer's I test (ST) was performed, and a result ≤5 mm after 5 minutes was defined as positive. The impact of FM was assessed by tender points (TP) count, the Widespread Pain Index (WPI), and the Symptom Severity score (SS) (3). Results: ST was positive in 91 patients (FM 11/66 (16.7%); Controls 32/92 (34.8%), p=0.009). 91 patients answered affirmatively to at least one of the three questions related to dry eye of the SQ (FM 54/66 (81.8%); Controls 37/92 (40.2%)), including 56 patients with negative ST (FM 43/55 (78.2%); Controls 13/60 (21.7%), p=0.000) (fig 1 ). By McM, 72 patients (FM: 35/45 (77.8%); Controls 37/82 (45.1%)) were classified as having dry eye, including 46 with negative ST (FM 27/36 (75.0%); Controls 19/53 (35.8%)). SQ and McM questionnaires were fairly well correlated (k =0.760, p=0.000). Logistic regression showed that for both SQ and McM, dry eye symptoms were correlated to age, actual ST results, and to the presence of FM (p<0.000). In FM, dry eye symptoms were correlated to the burden of FM (fig 2 ). Conclusions: This is the first study addressing the concordance between subjective symptoms and objective findings in the assessment of dry eye in FM. Our results show that dry eye symptoms are extremely frequent in FM, but are related to the severity of FM symptoms rather than to the results of Schirmer's test. References: Vitali C, Ann Rheum Dis 2002 Nichols KK, Cornea 2004 Wolfe F, Arthritis Care Res. 2010 Disclosure of Interest: None Declared